Establishment of a Decaplex PCR-Capillary Gel Electrophoresis Method for the Simultaneous Detection of Six Kinds of Genetically Modified Animals. (23rd November 2019) - Liu, Xiaofei; Qiu, Songyin; Li, Xiaolin; Liu, Dandan; Jing, Hongli; Wang, Qin; Lin, Xiangmei; Pan, Dengke; Shi, Ningning
Abstract: This study aimed to establish an event-specific multiplex PCR system using microsatellite markers and fluorescently labeled primers to detect six different genetically modified (GM) animal lines, including human lactoferrin GM cattle, human lysozyme GM cattle, human α-lactalbumin GM cattle, myostatin knockout pigs, phytase GM pigs, and ω-3 fatty acid desaturase gene GM pigs. Four different microsatellite loci for species identification, along with six GM animal-specific fragments, were selected as targets for primer design. The capillary gel electrophoresis results of multiplex PCR showed that the target fragments were amplified successfully. This high-throughput multiplex PCR detection system can be applied for the inspection and quarantine of GM animals.